How to strategically choose or combine augmented and virtual reality for improved online experiential retailing. Issue 3 (4th October 2021) - Hilken, Tim; Chylinski, Mathew; Keeling, Debbie I.; Heller, Jonas; de Ruyter, Ko; Mahr, Dominik
Abstract: Despite the promise of augmented reality (AR) and virtual reality (VR) to help experiential retailers align online and offline experiences, guidance on choosing or combining these technologies is lacking. In three experiments, we address this research gap by investigating the individual and combined impact of AR and VR on key marketing objectives. First, we establish that AR is more effective in stimulating purchase intentions than VR, due to its ability to support customers in fluent product‐focused mental imagery. Second, we demonstrate that VR is better suited for improving brand attitudes than AR, as it helps customers to form fluent context‐focused mental imagery. Third, we show that AR and VR, in combination, can improve both purchase intentions and brand attitudes, but only when the order of deployment is sequenced as AR then VR. This is due to greater alignment with the customer's online‐to‐offline journey in experiential retail. When deployed the other way around, we observe a detrimental impact on purchase intentions and a potential harmful impact on brand attitudes. Our research offers a nuanced theoretical perspective of AR and VR in marketing and provides experiential retailers with evidence‐based guidelines for leveraging AR and VR within their online retailing strategy.